Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

FINAL EDIT : Prove that if $p^z|n^2-1$

$$p^{x-z}(p^{z}-1)=\dfrac{ n^2-1}{p^z}-3$$ doesn't hold for any chosen values of $p,x,n$ and $z$.

Here $p>3$ is an odd prime , $x=2y+z, \ \{\{x,y,z\}>0\} \in \mathbb{Z}$ . There $n$ is an even number.

If the above statement is prove it will lead to a contradiction$^*$

$^*$: to understand the contradiction you need to read this :

EDIT : [History] : If anybody remembered the previous question of mine, I asked to prove $(p^x+3)(p^z-1)+4$ is not a perfect square. So I tried this $$p^{x+z}-p^x+3p^z+1=l^2$$ $$p^{x+z}-p^x+3p^{z}=l^2-1$$ $$p^z(p^{x}-p^{x-z}+3)=(l+1)(l-1)$$

Here its evident that $p^z$ divides either of $(l-1)$ or $(l+1)$. So let us assume as case (i) the $p^z|(l-1)$.

So let $k=\large \frac{l-1}{p^z}$, so when $k$ is decimal ( clearly $l-1$ is odd and $p^z$ is odd, so all the time the $k$ is not a integer ) ignore the case as it leads to a contradiction and proves it. Now look when $k$ is integer so the equation $$p^z(p^{x}-p^{x-z}+3)=(l+1)(l-1)$$ can be written as $$(p^{x}-p^{x-z}+3)=k(l+1)$$ $$p^{x}-p^{x-z}=k(l+1)-3.$$ After working on many examples, I have found an interesting pattern between the differences between the same odd number raised to different powers. For suppose we take an odd number $5$ and then work on the difference of the powers of it. So the difference seems to be of the form $O^n-O^{m}(n>m)$ ( where $O$ is an odd number ) . So let us call the set of all such differences $\mathfrak{D}^{n}_{O}$ set of all $\left\{O^n-O^{m}\right\}$ such that the integer $m$ runs from $0$ to $n-1$ . Here For example we can start writing all such differences to see an interesting property.

Fix $O=5$. Let us take and $n=1$ and $\mathfrak{D}^{1}_{5}$ is nothing but the set of 1 element $\left\{5^1-5^0=4\right\}$ Let us now take $n=2$ and $\mathfrak{D}^{2}_{5}$ is nothing but only 2 elements $\left\{5^2-5=20,5^2-5^0=24\right\}$. Let us now take $n=3$. So the $\mathfrak{D}^{3}_{5}$ is nothing but set of 3 elements $\left\{5^3-5^2=100,5^3-5=120,5^3-5^0=124\right\}$ \( Since for $n=3$ there are only two possible $m=1,2 (3-1=2)$. Let us now take $n=4$. So the $\mathfrak{D}^{4}_{5}$ is nothing but the set of 3 elements $\left\{5^4-5^3=500,5^4-5^2=600,5^4-5=620,5^4-5^0=624\right\}$. Let us now take $n=5$. So the $\mathfrak{D}^{5}_{5}$ is nothing but the set of 4 elements $\left\{5^5-5^4=2500,565-5^3=3000,5^5-5^2=3100,5^5-5=3120,5^5-5^0=3124\right\}$.

And so on for different values of $n$. If we observe we find that the elements of the sets follow a good pattern. After trying for many such numbers I came to know the pattern. Let me explain it sir. So let us write down all such $\mathfrak{D}^{n}_{5}$ $$\mathfrak{D}^{1}_{5}=\left\{4=5^0*(5-1)\right\}$$ $$\mathfrak{D}^{2}_{5}=\left\{20=5^1*(5-1),24=5^1*(5-1)+5^0*(5-1)\right\}$$ $$\mathfrak{D}^{3}_{5}=\left\{100=5^2*(5-1),120=5^2*(5-1)+5*(5-1),124=5^2*(5-1)+5^1*(5-1)+5^0(5-1)\right\}$$
$$\mathfrak{D}^{4}_{5} = \{500,600,620,624\}$$

Here each element can be written as $\{500=5^3*(5-1),600=5^3*(5-1)+5^2*(5-1),620=5^3*(5-1)+5^2*(5-1)+5^1*(5-1),624=5^3*(5-1)+5^2*(5-1)+5^1*(5-1)+5^0*(5-1) \}.$\ Similarly $$\mathfrak{D}^{5}_{5} = \{2500,3000,3100,3120 \}.$$\ Here also each element can be written as $\{ 2500=5^5*(5-1),3000=5^5*(5-1)+5^2*(5-1),3100=5^5*(5-1)+5^4*(5-1)+5^3*(5-1),120=5^5*(5-1)+5^4*(5-1)+5^3*(5-1)+5^2*(5-1)+5^1*(5-1),3124=5^5*(5-1)+5^4*(5-1)+5^3*(5-1)+5^2*(5-1)+5^1*(5-1)+5^0*(5-1) \} $

Any pattern ?? .

Yes there is a pattern sir. For any $O^{n}-O^{m}$ for any odd number $O$ and any integers $n,m (m<n)$ can be expressed as :

\begin{equation} O^{n}-O^{m}=\sum^{n-1}_{i=m} O^{i}*(O-1) \end{equation}

Now we can write the R.H.S of equation $$(p^{x}-p^{x-z}+3)=k(l+1)$$ as $$p^{x}-p^{x-z}= \sum^{x-1}_{x-z} p^i.(p-1)$$ After expanding the series and simplyifying we obtain $$p^{x-z}(p-1).\large\frac{p^x-1}{p-1}$$ $$p^{x-z}(p^z-1)$$

So we can equate to get $$p^{x-z}(p^z-1)=k(l+1)-3.$$

So we need to prove that both sides of the equation don't yield the same even number leading to a conrtradiciton. Hence I am trying that. I am here with a question again. Suppose we have an equation of this form $$p^{x-z}(p^{z}-1)=k(l+1)-3$$ where $p$ is an odd-prime, $z,y$ are integers and $y>0$ always ($x=2y+z, $ for some integer $x$ ) , $k$ is an odd number and $l$ is an even number.

So given such constraints and for any $p>3$ its well known that after substituting values of all variables its clear that both sides of the equation don't yield the same even number ( for any values ) . So how can we prove it ?.

I have been trying to prove it using congruences, but that didn't take me anywhere. So I wanted to ask it here.

Thank you.

share|cite|improve this question
I don't understand what you mean. Is there a problem with p = 5, z = 1, y = 1, k = 3, l = 40, for example? Both sides yield 120 – Cocopuffs Jun 14 '12 at 16:22
If I understand the problem correctly, the left side and the right side can hit the same even number. This is because the constraint $k(l+1)-3$ with $k$ odd and $l$ even says little about the right side. Example: Let $p=5$, $x=1$, $y=1$. The left side is $120$. Want $123=k(l+1)$, easy to arrange. – André Nicolas Jun 14 '12 at 16:23
@Cocopuffs : So given that constraints can you comment now sir ? – Iyengar Jun 14 '12 at 17:01
@ZevChonoles : Please don't close this question sir. I somehow clicked to close in hurry but later wanted to change this question. I have done it anyway. Thank you. – Iyengar Jun 15 '12 at 18:03
@Iyengar There are ladies here too. I don't think it's appropriate call everybody "sir" or "Mr." – user23211 Jun 22 '12 at 11:51

Edit: this only answers the old version of the problem. The question was changed so this answer is out of date.

The original problem was $$p^{x-z}(p^x-1)=\frac{n^2-1}{p^z}-3$$

Suppose we have a solution to the equation. The only hypotheses we need are that $p$ be any integer $\ge 2$, and $x>z>0$.

Then $$n^2=1+3p^z+p^x(p^x-1)$$ $$n^2=(p^x+1)^2-3(p^x-p^z)<(p^x+1)^2$$ $$n^2=(p^x-1)^2+p^x+3p^z>(p^x-1)^2$$ So we must have $$n^2=(p^x)^2$$ but this would imply $n^2=0 \pmod p$, which contradicts $n^2=1 \pmod p$ from the first equation above. So there cannot be any solution.

share|cite|improve this answer
Very clean answer sir, I didn't understand these things sir. 1) How do we obtain $\Delta^{\prime}=1+p^z(3+p^{2x-z}-p^{x-z})$ ?. I do know the general discriminant of $ax^2+bx+c$ which is $\Delta=b^2-4ac$ but how do we obtain that thing. What does reduced there mean ? . 2) How does $\Delta^'=(p^x)^2 \implies p^x-3p^z=1$ ? . Thanks a lot for your patience... – Iyengar Jun 18 '12 at 6:04
(1) The reduced discriminant is $\Delta'=\Delta/4=(b/2)^2-ac$. This is useful when we know that $b$ is even. (2) Subtract the equality $\Delta'=(p^x)^2$ from the definition of $\Delta'$ and you get this equation. – Generic Human Jun 18 '12 at 12:23
Sir how did you get $n^2=1+3p^z+p^x(p^x-1)$ in the first line. I don't understand that. – Iyengar Jun 19 '12 at 16:56
Multiply the original equation by $p^z$ and add $1+3p^z$ to both sides. – Generic Human Jun 19 '12 at 17:03
The original equation is $p^{x-z}(p^{z}-1)=\dfrac{ n^2-1}{p^z}-3 $. But I made a mistake there.. so it now leads to a disturbance of the proof of Mr.Generic Human. – Iyengar Jun 19 '12 at 18:38

First, if $x=z$ then $$ (p^x+3)(p^x-1)+4 = p^{2x}+2p^x+1=(p^x+1)^2 $$ which is always a square.

Second, the index is wrong in the sum $$ p^{x}-p^{x-z}= \sum p^i(p-1) $$ it should be from $i=x-z$ to $x-1$, and after expanding the series and simplifying we get $$ (p-1)p^{x-z} \sum^{z-1}_{i=0} p^i = p^{x-z}(p-1)\frac{p^z-1}{p-1} = p^{x-z}(p^z-1) $$ which we could see by factoring the left side.

share|cite|improve this answer
Yes sir you are right, Thanks a lot. – Iyengar Jun 15 '12 at 5:08
Really a very good observation, Zander. Thanks a lot sir, for your modification... – Iyengar Jun 15 '12 at 5:35

Since $p^z|n^2-1$, we could write $n^2-1=k(p^z)+m$ for some m,k where $m\lt p^z$, so we could plug this into the equation. Then we would get $p^{2y}(p^z-1)=k+{m\over p^2}-3 $, since the left hand side is integer, we need the right hand side to be integer. However since $m\lt p^2$, the quantity $m\over p^2$ cannot be integer, so the equation does not hold.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.